Analysis of the structural changes in domestic consumption of FUEL and energetic resources of Moscow - L. G. Moiseykina; E. S. Darda (Статистика и экономика, 2018)
Purpose of the study. The fuel and energy complex is one of the important components of the mechanism of functioning of the national economy in general and municipal economy in particular, since the main tasks of the complex include: provision of hot water supply all year round and heat during the winter period, meeting the needs of the population and municipal economy in gas, supply of gasoline and diesel fuel to satisfy consumers, as well as the supply of coal, peat, fuel oil and other fuels for the urban economy. An important role is played by enterprises of the fuel and energy complex in terms of providing jobs to the population. The fuel and energy complex of Moscow is one of the largest in Russia. A feature of its functioning is the concentrated consumption of gas, fuel, electricity, heat energy and other energy resources. The formation and development of the fuel and energy complex in Moscow is largely due to the rapidly developing economy of the megapolis – large-scale construction of housing and infrastructure, sustainable population growth entails a constant increase in consumption of fuel and energy resources. Monitoring the efficiency of the use of fuel and energy resources makes it possible to identify ways to reduce the volume of consumption to a level that allows, within the approved limit, to implement the planned rate of social and economic development of the city. Materials and methods. Information base of the research was made by statistical data characterizing the volume of consumption of certain types of fuel and energy resources in the market of the Moscow region. The methodological basis of the study is made up of statistical methods of analysis of structure and structural shifts, dynamics. Their use made it possible to conduct a thorough analysis of the differentiation of consumption of various types of fuel and energy resources, as well as structural changes in the differentiations in question. It made it possible to identify existing trends in the development of the fuel and energy complex in the capital region Results. The analysis allowed to identify the current trends in consumption of the main types of fuel and energy resources in Moscow, to assess the structure and structural changes in consumption of fuel and energy resources in Moscow, in order to assess the energy efficiency of the fuel and energy complex of the capital. Conclusion. The main goal of Moscow’s energy policy is to create an economically efficient, dynamically developing and financially sustainable fuel and energy complex equipped with advanced technologies and highly qualified personnel and meeting the requirements of the time and status of Moscow. Increasing the efficiency of the use of fuel and energy resources, for Moscow as one of the coldest capitals of the world, is becoming one of the priority tasks. Consequently, another task of developing the fuel and energy complex of the city is to expand the scale of the introduction of secondary energy resources and bring the indicator of their use to 50%. That is why, a comprehensive analysis of the dynamics and structure of consumption of fuel and energy resources will allow not only to assess the existing patterns of distribution and trends, but also as a consequence to form a highly effective energy strategy for the megacity.